On Modern Poetry : From Theory to Total Criticism. - Smith, Robert Rowland (Bloomsbury Publishing, 2012)
Alltoo often, the history of poetry criticism in the 20th Century is told as atale of two sides. While 'Lit crit' pored over the author's every line, 'Theory' stood on the shoulder of texts to gaze into the metaphysical mists. Drawingon the key insights of both Lit crit and Theory, On Modern Poetry tries to get beyond the oppositionbetween them, proposing instead a 'total criticism' that draws on all resourcesavailable. It combines 'analytic irony' with 'imaginative empathy' in orderto generate fresh insights. The themes discussed in the firstpart of the book include tradition, voice, rhyme, rh.